STRATEGI PENGELOLAAN BADAN USAHA MILIK DESA (BUMDES) DALAM MENINGKATKAN PENDAPATAN ASLI DESA: (Studi Kasus: Desa Bojonggede Kecapatan Bojonggede Kabupaten Bogor) - Nasdar Wijaya (Jurnal Wahana Bina Pemerintahan, 2023)
One way to succeed in village development is to increase village income. The size of the village income is influenced by the strategy undertaken by BUMDES in managing and maximizing the assets in the village. The Village (BUMDES) is a business entity whose capital is wholly or most of the capital owned by the village through direct participation from village assets that are separated in order to manage assets, services, and other businesses for the greatest welfare of the village community. The research design uses historical qualitative research methods. The variables studied were the BUMDes strategy and the increase in village original income. Data collection techniques using study documentation, observation and interviews. Informants taken in this study were the Village Head, Director of BUMDes, and the village community of Bojonggede. This paper describes the management strategy carried out by BUMDES in increasing village income. The strategies carried out by the Bojonggede Prosperous BUMDES are strategy formulation, strategy implementation. The strategy was carried out by the BUMDES of Bojonggede Village both in the field of goods and services. From the results of the study, it can be concluded that the management strategy that has been carried out by the prosperous Bojonggede BUMDes cannot run well because the prosperous Bojonggede BUMDes cannot increase the original income of Bojonggede Village in 2019.